Conference Approval System (e-CoAS) / Nor Hidayah Rahim - Rahim, Nor Hidayah (2015)
Nowadays, in managing the conference application for UiTM Lecturers who want to attend in the conference is still use manual process where they need to fill in the application form and walked in the Unit Latihan office to submit the application detail and then Unit Latihan needs to pass by hand to the evaluators. However, through e- CoAS that is a web-based system technology where management of conference application in UiTM Terengganu becomes easier, faster and more efficiently to manage the applications. The adapted of Waterfall Model is used in order to help in developing this system. This methodology consists of 5 phases which are requirement definition phase, design phase, development phase, testing phase and documentation phase. When using adapted waterfall model as the guideline to develop this Conference Approval System (e-CoAS), it make the processes of development of e- CoAS becomes easier and simple for programmers to make it works. The evaluation has been conducted by three expert users and through it, the evaluation was produced the comment and suggestion of the system. The evaluation also conducted based on the questionnaires given to the 30 respondents which consist of UiTM students to evaluate the system. It is found that the system is able to use based on the result that evaluated through on the effectiveness, efficiency, satisfaction, navigation and interface. Based on the respondents analysis, showed that the highest mean based on the user feedback is item interface which is 4.27 (SD= 0.7). As a conclusion, e-CoAS give more benefits for the users and hopefully will contribute further in this evolving for better management in conference approval system.